A New Type of Coincidence and Common Fixed-Point Theorems for Modified ð-Admissible ð©-Contraction Via Simulation Function - Sahil Arora; Manoj Kumar; Sanjay Mishra (Journal of Mathematical and Fundamental Sciences, 2020)
In this manuscript, we introduce the concept of modified Î±-admissible contraction with the help of a simulation function and use this concept to establish some coincidence and common fixed-point theorems in metric space. An illustrative example that yields the main result is given. Also, several existing results within the frame of metric space are established. The main theorem was applied to derive the coincidence and common fixed-point results for Î±-admissible ð’µ-contraction.